Worlds apart: Plant health and One Health and a path to convergence - Solveig Danielsen; Urs Schaffner; Jakob Zinsstag (CABI One Health)
Abstract Plant health is increasingly recognized as a vital part of One Health. Yet, action lags behind recognition. Historically focused on health service provision, zoonotic diseases, and antimicrobial resistance, One Health often overlooks plant health in strategic plans. The paradox? Cross-sectoral approaches, core to One Health, are already used in plant health fields like agroecology, sustainable food systems, and integrated landscape management – just not under the One Health banner. The disconnect between the worlds of One Health and plant health limits recognition of interconnected health challenges, obscures critical knowledge gaps, and stifles opportunities for synergy. By staying outside One Health’s framework, the “plant world” misses the political and institutional clout of bodies like the Quadripartite and the One Health High-Level Expert Panel, essential for driving global support. FAO and other plant-focused stakeholders could assert their role more clearly in tackling severe One Health issues like pesticide risks, mycotoxins, invasive species, and biodiversity loss. Barriers to change persist. Plant professionals often do not associate their work with One Health, and traditional One Health actors may fail to see the value of integrating plant health. However, there are signs that change is gradually happening. Ideas and initiatives are surfacing, demonstrating different ways in which One Health approaches can be used in plant health, such as to ensure all aspects of a problem are considered in looking for plant health solutions, or to integrate plant health in a One Health biosecurity policy and regulatory framework. The planning of the next phase of the Quadripartite One Health Joint Plan of Action presents a timely opportunity to rethink strategies and break down barriers that currently limit true cross-domain integration. One Health impact statement Although plant health is included in One Health’s definition, significant conceptual, disciplinary, and power-related gaps hinder its practical integration, reinforcing a persistent focus on zoonoses and antimicrobial resistance (AMR). The Quadripartite collaboration on One Health, as a global agenda-setting entity, must address the fragmentation within the United Nations (UN) system that limits cross-domain coordination and the effective inclusion of plant health. This paper adds nuance and perspective to the debate, and challenges decision-makers, researchers, practitioners and funders to broaden One Health’s scope, recognizing plant health as essential to achieving its goals. A stakeholder process is proposed to build consensus on the definition of One Health, as articulated by the One Health High-Level Expert Panel (OHHLEP): “optimizing the health of humans, animals, plants, and the environment.”